Transplantation of PDGF-AA-Overexpressing Oligodendrocyte Precursor Cells Promotes Recovery in Rat Following Spinal Cord Injury - Yao, Zong-Feng; Wang, Ying; Lin, Yu-Hong; Wu, Yan; Zhu, An-You; Wang, Rui; Shen, Lin; Xi, Jin; Qi, Qi; Jiang, Zhi-Quan; Lü, He-Zuo; Hu, Jian-Guo (Frontiers in Cellular Neuroscience, 2017)
Our previous study showed that Schwann cells (SCs) promote survival, proliferation, and migration of co-transplanted oligodendrocyte progenitor cells (OPCs) and neurological recovery in rats with spinal cord injury (SCI). A subsequent in vitro study confirmed that SCs modulated OPC proliferation and migration by secreting platelet-derived growth factor (PDGF)-AA and fibroblast growth factor-2. We also found that PDGF-AA stimulated OPC proliferation and their differentiation into oligodendrocytes (OLs) at later stages. We therefore speculated that PDGF-AA administration can exert the same effect as SC co-transplantation in SCI repair. To test this hypothesis, in this study we investigated the effect of transplanting PDGF-AA-overexpressing OPCs in a rat model of SCI. We found that PDGF-AA overexpression in OPCs promoted their survival, proliferation, and migration and differentiation into OLs in vivo. OPCs overexpressing PDGF-AA were also associated with increased myelination and tissue repair after SCI, leading to the recovery of neurological function. These results indicate that PDGF-AA-overexpressing OPCs may be an effective treatment for SCI.